Glassy, amorphous and nano-crystalline materials thermal physics, analysis, structure and properties - Sestak, Jaroslav; Mares, Jiri J.; Hubik, Pavel; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
Glassy, Amorphous and Nano-crystalline Material: Thermal Physics, Analysis, Structure and Properties includes twenty-one chapter contributions from an international array of distinguished academics based in Asia, Australia, Eastern and Western Europe, Russia, and the USA. The book provides a coherent and authoritative overview of cutting-edge themes involving the thermal analysis, applied solid-state physics and the micro-crystallinity of selected materials and their macro- and microscopic thermal properties. Selected chapters featured in the book include: Essential attributes of glassiness regarding the nature of non-crystalline solids; Aspects of vitrification, amorphization, disordering and the extent of nano-crystallinity; The basic role of thermal analysis in polymer physics; Classical and quantum diffusion and their application to the self-organized oscillatory reactions; Specificity of low temperature measurements applied to nano-crystalline diamante; Thermophysical properties of natural glasses at the extremes of the thermal history profile; Phenomenological meaning of temperature as background for the history and development of thermal analysis and calorimetry. Advanced undergraduates, postgraduates and researchers working in the field of thermal analysis and calorimetry will find this contributed volume invaluable.
Electronic reproduction.
Keywords: Semiconductor nanocrystals; Amorphous semiconductors; Nanostructured materials; Electronic books